소득보장 및 사회통합을 위한 청년 참여소득의 도입 방안 - 문성호; Moon Sung Ho; 정지윤; Jung Ji Yun; 한지연; Han Ji Yeon; 노자은; Roh Ja Eun; 노지혜; Noh Ji Hye (청소년복지연구, 2021)
본 연구의 목적은 청년 개인의 소득을 보장하고 사회통합을 이루기 위한 참여소득의 도입 방안을 제안하는 것이다. 연구의 목적을 달성하기 위해 기존 청년정책의 특성과 한계를 살펴보고, 참여소득의 효과 및 가치, 그리고 국외 유사한 실행경험을 포괄적으로 분석하였다. 이를 바탕으로 청년 참여소득의 3대 기본방향과 4대 실행 전략을 제시하였다. 청년 참여소득의 기본방향은 소득기준과 관계없이 미취업ㆍ비전형 근로 청년 ‘누구나’ 참여 가능, 시장이 아닌 사회에 기여, 그리고 지역사회 기반 운영을 통한 지역 공동체의 활성화 도모이다. 대상, 활동범위, 운영체계, 급여 및 재정으로 구분하여 제시한 청년 참여소득의 실행 전략은 첫째, 미취업ㆍ비전형근로 청년들을 그 대상으로 선정하였다. 둘째, 활동의 범위는 성장지원, 사회참여, 공공안전, 가족돌봄 활동을 포함하였다. 셋째, 참여소득의 운영체계는 중앙 및 지방정부의 역할을 강조하면서 중앙단위의 총괄운영기관 신설을 제안하였다. 마지막으로 급여 및 재정은 최저임금과 생계급여를 고려하여 월 90만원 이내의 소득을 보장받을 수 있도록 설계하였다. 이와 함께 재정과 관련해서는 참여기금의 조성 방안을 검토하였다. 본 연구에서 도입을 제안한 청년 참여소득은 소득보장을 통해 불안정한 고용과 실업정책의 한계를 보완할 수 있으며, 지역사회에 필수 사회서비스를 제공하여 사회통합을 이루는 밑거름이 될 수 있을 것이다. This study aimed to propose an introduction plan of youth participation income for income security and social integration. For this purpose, the features and limitations of youth policies were examined. Also, the effect and value of participation income, and overseas similar cases were comprehensively analyzed. In result, three basic directions and four implementation strategies of youth participation income were suggested. The basic directions of youth participation income were as follows; ‘anyone can participate regardless of income standard’, ‘someone contributes to society rather than the market’, and ‘local communities are promoted through community-based operation’. In the first implementation strategy, unemployed and non-standard working youths were selected as the target of youth participation income. Second, the scope of activities included growth support, social participation, public safety, and family care. Third, the operating system of participation income suggested establishing the general operating organization and emphasized the role of the central and local governments. Lastly, wage and finance, considering a minimum wage and a living wage were designed for securing up to 900,000 won per month. With regard to finance, the plan to raise fund through participating was reviewed. Youth participation income can compensate for the unstable employment and complement the limitations of unemployment policies by guaranteeing income. In addition to this, it would be able to be foundation of integrating society through providing essential social services to local communities.